Frequency of mandibular asymmetry in panoramic radiographs in the city of Cuenca, Ecuador - Galarza Galarza, Micaela Jeniffer (2023)
Objective: This study aims to determine the frequency of mandibular asymmetries using digital panoramic radiographs that display complete teeth. Material and methods: A descriptive, observational, and retrospective cross-sectional study was conducted. The records of all digital panoramic radiographs from patients aged 18 to 59 years, taken at the Dental Image radiographic center during the period 2016-2020, were reviewed. Panoramic radiographs were evaluated for the presence of mandibular asymmetry using the Habets index. Digital radiographic tracing was employed to assess variables including ascending ramus height (C+R), mandibular ramus height (RH), and condylar height (CH). Symmetrical and asymmetrical radiographs were compared. Results: Out of the total sample of 1000 radiographs analyzed, the predominant age group was 34-41 years, constituting 301 radiographs (30.1%). Additionally, in terms of asymmetry based on gender, males exhibited a predominance, with 33 (6.6%) symmetrical radiographs and 467 (93.4%) asymmetrical radiographs. Conclusions: The study revealed a prevalence of height asymmetry in the right ascending ramus, with greater height observed in males (64.8 mm). These values demonstrated statistical significance in relation to both age and gender.